The Role of Artificial Intelligence Technology in Improving English Writing Skills of Language Education Students - Yuniantoro, Gatot (Universitas Syiah Kuala, 2025)
This study aims to determine the role of artificial intelligence technology in improving English writing skills of language education students. The population in this study were 280. The sample consisted of 30 taken by random sampling. The data collection technique used a Likert scale questionnaire. Data analysis techniques with Analysis techniques with simple correlation tests, simple regression tests, determinant coefficient tests, and t tests. The result of the study is that there is an influence of artificial intelligence technology on the writing abilities of English language education students.